Respuesta :
Answer:
x = 10 x = -2
Step-by-step explanation:
(x - 4)^2 = 36
Take the square root of each side
sqrt((x - 4)^2) =±sqrt( 36)
x-4 = ±6
Separate into two equations
x-4 =6 x-4=-6
Add 4 to each side
x-4 +4 =6+4 x-4+4 = -6+4
x = 10 x = -2
Answer: The answer is x = 22.
Step-by-step explanation:
To solve this equation, we first have to simplify the left side of the equation.
To do this, we should distribute the 2 into the parentheses (this means multiplying each of the terms inside the parentheses by 2). If we do this, we get:
2x - 8 = 36
Next, we should add 8 to both sides in order to get the variable term isolated on the left side. If we do this, we get:
2x = 44
Then, we should divide both sides of the equation by 2 in order to get rid of the coefficient on the variable. This gives us:
x = 44/2 = 22
Therefore, your answer is that x = 22.
Hope this helps!